Hyperinsulinemic euglycemic clamp in anesthetized rat : A protocol for rat in vivo FDG PET studies - Jalo, Anna (My University, 2021)
Obesity and physical inactivity are major public health issues in the population of the western countries. These conditions increase the risk for the development of insulin resistance and type 2 diabetes mellitus and lead to other complications, such as cardiovascular diseases, diabetic retinopathy, nephropathy, and neuropathy. The “gold standard” for measuring tissue specific insulin sensitivity in vivo is to measure tissue glucose uptake using medical imaging modality positron emission tomography (PET) combined with the hyperinsulinemic euglycemic clamp. In this procedure insulin is administered to cause hyperinsulinemia while variable glucose concentration is administered to maintain euglycemia. Using radio-labeled glucose analogue tracer 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG) the amount of glucose taken up by specific tissues can be determined using PET. Even though the clamp method was adapted to preclinical studies with rats already in 1983, the preclinical method lacks universal guidelines and is subject to variations specific to the laboratory conducting the study. The aim of this study was to establish a protocol for the Sprague Dawley laboratory rat strain for the hyperinsulinemic euglycemic clamp in combination with [18F]FDG PET imaging. Different insulin infusion rates were compared to define the optimum conditions for the clamp and the set up for combining the insulin clamp with PET imaging was created. Of the tested insulin infusion conditions, the two-stepped priming with 120 mU/kg/min for 2 minutes and 60 mU/kg/min for 2 minutes, followed by continuous infusion of 12 mU/kg/min produced the shortest time to reach and maintain euglycemia. A shunt system was created to accommodate for an automated blood sampling system to measure online in vivo blood radioactivity during the PET imaging. This work describes a basic clamp protocol that can be adjusted for more rat strains and other species of laboratory animals. The shunt system can be used for dynamic PET studies generally to provide an arterial input function without the need to draw blood from the animal.

Liikalihavuus ja fyysinen liikkumattomuus ovat suuri kansanterveydellinen ongelma länsimaiden väestössä. Nämä lisäävät insuliiniresistenssin sekä tyypin 2 diabeteksen riskiä ja voivat johtaa muihin komplikaatioihin, kuten sydän- ja verisuonitauteihin ja diabeteksen liitännäissairauksiin. Kudoskohtaisen insuliiniherkkyyden määrittämisen parhaana standardimenetelmänä pidetään insuliini-clamp-tutkimusta yhdistettynä radiolääketieteelliseen kerroskuvausmenetelmään eli positroniemissiotomografiaan (PET). Tässä menetelmässä annostellaan tutkittavaan insuliinia hyperinsulinemian aikaansaamiseksi samalla, kun glukoosi-infuusiolla pidetään verensokeri tasaisena euglykeemisellä alueella. Kudoskohtaista glukoosin käyttöä voidaan mitata radioaktiivisilla isotoopeilla leimatuilla sokerijohdannaisilla yhdistettynä PET-menetelmään. Vaikka tämä menetelmä otettiin käyttöön prekliinisessä koe-eläintutkimuksessa jo vuonna 1983, ei vakiintunutta tutkimusmenetelmää ole määritetty kuten kliinisissä potilastutkimuksissa. Tämän tutkimuksen tavoitteena oli luoda standardoitu tutkimusmenetelmä insuliini-clamp-tutkimukseen rotalle. Tutkimuksessa vertailtiin erilaisia insuliinin infuusiomääriä optimaalisen antomäärän määrittämiseksi. Tutkimuksessa selvitettiin mahdollisimman tehokas infuusiomäärä, jotta euglykeeminen tila saavutettaisiin mahdollisimman nopeasti. Testatuista insuliininantomääristä kaksivaiheinen ”priming”, jossa annettiin insuliinia ensin 2 minuuttia 120 mU/kg/min infuusionopeudella ja seuraavaksi 2 minuuttia 60 mU/kg/min infuusionopeudella ennen ylläpitotasolle laskua (12 mU/kg/min), tuotti nopeimman tavan saavuttaa verensokerin euglykeeminen tasapainotila. Tutkimuksen osana luotiin myös tarvittava letkusto, jotta verta voidaan kierrättää kehon ulkopuolella automaattisen veren radioaktiivisuusmittarin läpi ilman verenhukkaa. Tässä työssä kuvaillaan clamp-protokolla, jota voidaan tarpeen mukaan muokata käytettäväksi useampien rottakantojen tai muiden laboratorioeläinlajien kanssa. Veren radioaktiivisuuden mittaamista automaattisella mittarilla voidaan hyödyntää myös muissa kuin sokerianalogimerkkiainetutkimuksissa veren kineettisen mallintamisen määrittämiseksi.
Keywords: insulin resistance, hyperinsulinemic euglycemic clamp, microsurgery, rat, PET